Role of bisphosphonates in the management of bone metastases. The summary of clinical trials - Serkies, Krystyna (Contemporary Oncology/Współczesna Onkologia, 2001)
The results of clinical trials addressing the efficacy of bisphosphonates: clodronate and pamidronate in patients with bone metastases are presented. In breast cancer and prostate cancer bisphosphonate therapy produced significant reduction in the incidence of skeletal metastases and associated morbidity as well as longer progression-free survival as compared to placebo group. Additionally, this therapy produced pain relief and less frequent need for radiation therapy in the painful osseous metastases. In consequence, the use of bisphosphonates is associated with increased patient performance status and quality of life. The treatment duration, routes of drug administration in long-term use, and cost of bisphosphonate treatment are presented. The role of oral bisphosphonates in prevention of osseous metastases in breast cancer patients is also discussed.